ANALISIS KOMPETENSI, PENGENDALIAN INTERNAL DAN MOTIVASI BERPRESTASI TERHADAP KINERJA PEGAWAI BADAN PERENCANAAN PEMBANGUNAN DAERAH PROVINSI RIAU DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING - Sahrul, Sahrul (Jurnal Tepak Manajemen Bisnis, 2017)
This research was conducted with explanatory approach where research aims to examine the causality between variables that describe a particular phenomenon and examine whether the variable competence, internal control and achievement motivation impact directly or indirectly on employee performance variables Bappeda Riau province with organizational commitment as an intervening variable. Respondents in the study amounted to 116 people using proportionate stratified random sampling technique where sampling of members of the population at random and stratified proportionally by means of statistical tests using path analysis (path analysis).The results showed that partial variable competence, internal control and achievement motivation direct influence on employee performance. Partial variable competence, internal controls directly influence organizational commitment while achieving motivation variable does not directly influence organizational commitment. Furthermore, through the organizational commitment as an intervening variable, variable competence, internal control and achievement motivation indirect effect on employee performance Bappeda Riau Province.